Prevalence of Proteinuria in Owned Dogs from Italy: A Multicentric Study. (19th March 2019) - Gizzarelli, M.; Roura, X.; Scarpa, P.; D'Ippolito, P.; Foglia Manzillo, V.; Oliva, G.; Tarducci, A.; Borrelli, A.; Melis, G.; Quintavalla, F.; Uva, A.; Guarraci, A.; et al.
Abstract : Even though proteinuria is related to different causes, when it is persistent and associated with inactive urinary sediment, it is primarily due to kidney disease. Early detection of proteinuria allows us to identify several pathological conditions. The aim of the study was screening a canine population not known as being proteinuric, by the urinary dipstick. The study was carried out in seven Italian veterinary clinics during a period of six weeks. Dogs were enrolled with no restriction of sex or age. Females in estrus, dogs with signs of genitourinary diseases, or those previously diagnosed with proteinuric nephropathy were excluded. Dogs were considered "nonproteinuric" (NP) in case of negative dipstick test or "suspected proteinuric" (SP), if positive at the dipstick. When possible, proteinuria was confirmed by UPC ratio. A total of 1156 dogs were evaluated: 414 were from northern Italy and 742 from southern Italy. Based on dipstick test, 655 (56.6%) dogs were NP, while 501 (43.3%) were SP. Among the NP dogs 225 out of 414 (54.3%) were in northern Italy and 430 of 742 (57.9%) in southern Italy. One hundred eighty-nine of 414 (45.7%) SP dogs were identified in northern Italy and 312 of 742 (42.1%) in southern Italy. No statistical difference was found between the North and the South of Italy. UPC was available in 412 out of 501 SP samples: proteinuria was confirmed in 263 (63.86%) samples. Results from our study showed a high percentage of suspected proteinuric dogs, apparently not affected by renal diseases, together with the absence of statistically significant differences based on geographical area.